Physiotherapy treatments for the patient with Bankart lesion repair: a case report study - Govinda Vittala; Muhammad Adrian Putra Rachman; Ni Luh Veni Rahayu; Ni Komang Mega Junianti; Emily Devina Kartawijaya; Ni Made Lidia Swandari; Putu Ayunia Laksmita (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Bankart lesion is torn in the anterior membrane covering the shoulder joint (labrum) due to continuous dislocation of the shoulder joint forward. Bankart lesions can occur due to sports activities that use the front of the shoulder, such as javelin throwing. It is not uncommon for injuries to javelin-throwing athletes to require physiotherapy treatment so they can return to playing javelin-throwing. Aim: This study aims to determine the effectiveness of the training program such as ultrasound therapy and transcutaneous electrical nerve stimulation (TENS), active assisted range of motion (ROM) exercises, active assisted ROM exercises against gravity, strengthening exercises, wall climbing, and open cage exercises. to tourists who are javelin throwing athletes who experience Bankart lesions. Case Report: In this case, a 42-year-old man from France came to the physiotherapy clinic complaining of pain, stiffness, and limited movement of the right shoulder joint. The patient underwent surgery for Bankart shoulder repair on his right shoulder on October 16th, 2022, due to repeated dislocations three times during javelin throws. The patient has limited movement and pain in the right shoulder. In addition, the right hand also does not swing when walking. On static inspection, the chest, shoulder, and right arm are smaller (atrophied) and positioned lower than the left. There is an incision in the anterior deltoid area (post-Bankart repair shoulder). Intervention modalities included ultrasound therapy applications and transcutaneous electrical nerve stimulation (TENS). Exercise therapy includes active assisted ROM exercises, active assisted ROM exercises against gravity, strengthening exercises, wall climbing, and open cage exercises. Result: After interventions, the patient’s recovery condition improved. An exercise program designed and implemented on patients for two weeks has slowly raised the patient's self-confidence and increased the patient's ability to perform physical activities. Conclusion: The physiotherapy intervention program for a Bankart lesion patient showed an improvement in the patient’s condition, with an increase in ROM, an increase in muscle strength, and a decrease in perceived pain.